2012
DOI: 10.1002/jca.21231
|View full text |Cite
|
Sign up to set email alerts
|

Increment of hematopoietic progenitor cell count as an indicator of efficient autologs stem cell harvest in patients with multiple myeloma

Abstract: We previously showed that hematopoietic progenitor cell (HPC) count is a useful surrogate for the timing of autologs stem cell collection (ASCC). We investigated the role of HPC count increment in predicting the time for optimal ASCC in patients with multiple myeloma (MM). Between May 2002 and January 2011, 138 patients with MM who underwent ASCC after mobilization with cyclophosphamide (4 g/m(2)) and granulocyte-colony stimulating factor at Asan Medical Center. HPC monitoring was started on the 10th day of cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…However, the data analysis indicated that increase in HPC count, either by slope or by ratio, was not a reliable indicator of efficient autologous HSC harvest, although a trend was found. These findings were in contrast to those reported in a previous study by Jo et al, 21 which shows that >2/mm 3 a day increase in HPC count is associated with fewer number of apheresis procedures required for obtaining optimal autologous HSC harvest in myeloma patients. The amount of increase in CD34 + cell count required for efficient autologous HSC harvest could not be analyzed in this study due to missing data.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the data analysis indicated that increase in HPC count, either by slope or by ratio, was not a reliable indicator of efficient autologous HSC harvest, although a trend was found. These findings were in contrast to those reported in a previous study by Jo et al, 21 which shows that >2/mm 3 a day increase in HPC count is associated with fewer number of apheresis procedures required for obtaining optimal autologous HSC harvest in myeloma patients. The amount of increase in CD34 + cell count required for efficient autologous HSC harvest could not be analyzed in this study due to missing data.…”
Section: Discussioncontrasting
confidence: 99%
“…There is evidence that the bone marrow microenvironment, containing endothelial cells, contributes to proper HSC function, including regeneration after injury caused by chemotherapy . Myelosuppression resulting from cytostatic agents is accompanied by the destruction of bone marrow vasculature; microvessels are reconstructed together with the recovery of hematopoiesis . Moreover, the angiogenic factors including angiopoietins 1, 2, and vascular endothelial growth factor play key roles in the process of mobilization of CD34+ to the peripheral blood .…”
Section: Discussionmentioning
confidence: 98%
“…In previous studies, the optimal cut-off level of the HPC count varied from 5 to 50/ µL [5,8,12,13]. Jo et al reported that a rate of HPC increase of more than 2.0/µL/day is a good indicator [10]. Furthermore, Letestu et al reported that when the HPC count is between 0 and 30/µL, direct enumeration of the CD34+ cells is required for decision making [8].…”
Section: Discussionmentioning
confidence: 99%
“…Automatic cell analyzers with the immature myeloid information (IMI) channel provide the hematopoietic progenitor cell (HPC) count, which is a surrogate marker of CD34+ cells, and can be obtained within only a few minutes and do not require monoclonal antibodies [2][3][4]. Several reports have demonstrated that the HPC count is correlated with CD34+ cell count and is a useful indicator of the optimal timing of PBSCH [5][6][7][8][9][10]. The final decision on…”
Section: Introductionmentioning
confidence: 99%